УСОВЕРШЕНСТВОВАНИЕ ПРАВОВОГО РЕГУЛИРОВАНИЯ ИНОСТРАННЫХ ИНВЕСТИЦИЙ В УКРАИНЕ - Светличная, Юлия Александровна (SUPREMANCE OF LAW, 2017)
In Ukraine, there are several levels of legal regulation of investment activities: national, international, regional, sectoral. I here are contradictions and inconsistencies between various regulations adopted in the form of laws, decrees of the head of the state, the government, other bodies of the central executive power and local government bodies and local self-government bodies concerning investment activities that hamper the investment process. The article proves the necessity of codification of investment legislation by adopting the Investment Code of Ukraine.
Keywords: investment; investment activity; state; business entities; codification; investment legislation